Manajemen Desain Penataan Lingkungan Berwawasan Green School di Raudlatul Athfal Raudlatul Ulum Ganjaran Gondanglegi Malang - Nikmahtul Khoir Tri Yulia; I’anatut Tholibah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Pesantren Mathali'ul Falah Pati, 2022)
PAUD environmental design management in terms of procedural planning concepts. This study aims to describe the environmental design management of PAUD green schools with insight, the waste management process towards learning activities and the supporting and inhibiting factors of waste management. This study used a qualitative research approach with descriptive data and a type of case study research (case study). Research result. Management design linkages such as place arrangement, indoor and outdoor displays are in accordance with procedural assessment standards. The waste management process for learning can focus on the character of children to become stronger to always love the environment. As for the specifications of the 3-R method as findings (1) Reuse reuses waste that is still functioning, especially used bottle feeding as a roof (2) reduces efforts to minimize waste used by children such as eating together with banana leaf mats. (3) Recycle manages useful products, especially towels, into flower pots. Supporting factors for waste management include solid teamwork, financing processes, supporting facilities and exemplary teachers. Meanwhile, the obstacle is the lack of integration in a more intensive learning process for children. Conclusions and suggestions can provide direction in keeping the environment clean, and even more creative in utilizing waste. manage waste and create works of art that sample high-value creativity.